KONSEP PENDIDIK MENURUT HAMKA - Siti Rahayu (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this study is to see how far the concept of educators according to Hamka in terms of meaning, the nature of educators, the nature of educators, duties and responsibilities of educators according to Hamka in order to overcome educator problems that often occur today. The research method uses qualitative methods, namely literature review. Researchers sought information from various Hamka books, as well as about educators, as well as from journals related to Hamka. This research is limited to the nature of educators, the nature of educators, the duties and responsibilities of educators, and how far the concept of educators according to Hamka in order to add insight to readers and the discussion does not widen from the object of research. This research shows that the concept of educator according to Hamka emphasizes the effort to become a good educator is the Amanah who does not prioritize material over everything hoping for God's Pleasure, so that there is a common thread of the concept of educator according to Hamka with Hamka's life journey and what is conveyed in his books. Furthermore, the current condition of an educator can apply what Hamka said for the advancement of student achievement, an institution, and the nation and to achieve a much better life.